The Dynamics of the Implementation of the 2024 Election on the Implementation of the 2019-2024 Legislative Function in Building the Harmonization of Indonesian Law - Ansori, Moh Reza; Nisa Syafithri, Firda; Dinul Faqih, Moch (Zona Law And Public Administration Indonesia, 2024)
Legal harmonization is the process of harmonizing various laws and regulations to avoid norm conflicts and ensure consistency in the national legal system. Legislation in the 2024 election year will be in a very worrying state. The DPR and the government as institutions tasked with discussing bills will experience many obstacles. Legislation neglect will become a disease of the DPR and the government every year. This research is to find out the dynamics of the 2024 elections affecting the implementation of the legislative function by the DPR for the 2019-2024 period as well as the influence of the 2024 elections on the implementation of the 2019-2024 legislative function in building harmonization of Indonesian law and the obstacles faced by the DPR for the 2019-2024 period in carrying out the legislative function during preparing and holding the 2024 elections. This research uses a normative juridical method with a case approach. The results of the research can be concluded that the dynamics of organizing the 2024 elections affect the implementation of the legislative function by the DPR for the 2019-2024 period, including experiencing many obstacles because the legislative experience so far shows that there is often a lack of legislation in the formation of laws and regulations. In the orderly formation of laws and regulations, the DPR only reaches the planning stage. Meanwhile, a bill must not only be planned, but also drafted, discussed, passed, and promulgated. The fate of legislation in the 2024 election year will be in a very worrying state. The DPR and the government as institutions tasked with discussing the bill will experience many obstacles. The influence of the 2024 Election on the implementation of the 2019-2024 legislative function in building harmonization of Indonesian law is the disharmony between the laws and regulations formed and the laws and regulations that have been in force before can cause uncertainty in the implementation of the law